2019
DOI: 10.1002/jhbp.601
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐encapsulated microRNA‐4525, microRNA‐451a and microRNA‐21 in portal vein blood is a high‐sensitive liquid biomarker for the selection of high‐risk pancreatic ductal adenocarcinoma patients

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy with poor prognosis. This is due to late diagnosis and lack of reliable prognostic biomarkers. In this study, we focused on exosomal microRNA (miRNA) in portal vein blood (PVB) as a potential biomarker to identify patients at high‐risk for recurrence and poor postoperative outcome. Methods Exosomal miR‐4525, miR‐451a and miR‐21 expressions were assessed using PVB and peripheral blood (PB) collected from 55 PDAC patients during curative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 27 publications
0
62
0
Order By: Relevance
“…Furthermore, it has also been reported that miRNA-16a and miRNA-196a, together with CA19-9 [60], provided a positive outcome towards the identification of stage I of PC [61], suggesting that these exosomal microRNAs can also be used as PC peripheral biomarkers [62]. Also, in Kawamura's study, miR-4525, miR-451a, and miR-21 derived from portal vein have been proved possible biomarkers to determine the likelihood of recurrence and poor survival in patients with pancreatic cancer [63]. Furthermore, CKAP4, a DKK1 receptor, and secreted by exosomes, was also found to be a potential biomarker for pancreatic cancer [64].…”
Section: Exosomes Are Promising Tools To Be Used As Pancreatic Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, it has also been reported that miRNA-16a and miRNA-196a, together with CA19-9 [60], provided a positive outcome towards the identification of stage I of PC [61], suggesting that these exosomal microRNAs can also be used as PC peripheral biomarkers [62]. Also, in Kawamura's study, miR-4525, miR-451a, and miR-21 derived from portal vein have been proved possible biomarkers to determine the likelihood of recurrence and poor survival in patients with pancreatic cancer [63]. Furthermore, CKAP4, a DKK1 receptor, and secreted by exosomes, was also found to be a potential biomarker for pancreatic cancer [64].…”
Section: Exosomes Are Promising Tools To Be Used As Pancreatic Cancermentioning
confidence: 97%
“…miR-4525, miR-451a, and miR-21 Diagnosis [63] The plasma of patients with primary pancreatic ductal adenocarcinoma and plasma from healthy controls.…”
Section: Exosomes Are Essential In Pancreatic Cancer Treatmentmentioning
confidence: 99%
“…Goto et al (50) reported that exosomal miR-21 isolated from pancreatic juice using ultracentrifugation could also differentiate PDAC and chronic pancreatitis (CP). The patients with PDAC had a higher level of exosomal miR-451 than the HP, and the expression level of miR-451 wassignificantly correlated with recurrence and survival time (48,51). Plasma exosomal miR-196a and miR-1246 also showed diagnostic value for localized pancreatic cancer (52).…”
Section: Clinical Applications Of Exosomes Exosomes As Biomarkers Formentioning
confidence: 94%
“…Many studies have highlighted the possibility of clinical translation of exosomal biomarkers in PDAC ( Table 2). Plasma exosomal miR-21 could be used to differentiate patients with PDAC, intraductal papillary mucinous neoplasm (IPMN) and healthy participants (HP) (48,49). Goto et al (50) reported that exosomal miR-21 isolated from pancreatic juice using ultracentrifugation could also differentiate PDAC and chronic pancreatitis (CP).…”
Section: Clinical Applications Of Exosomes Exosomes As Biomarkers Formentioning
confidence: 99%
“…Previous studies indicate that miRNA-451a, miRNA-21, and miRNA-10b are highly expressed in pancreatic cancer cells and pancreatic cancer tissues. [12,36,37] Therefore, MB-451a, MB-21, and MB-10b were designed to probe these miRNAs (Table S2, Supporting Information). The ability of MBs to detect miRNAs was first evaluated in homogeneous solution.…”
Section: Preparation Of Fvs and In Situ Detection Of Mirnas In Exosomesmentioning
confidence: 99%